Agracejo - Many species, little ethnobotanical and ethnopharmacological information - Rodríguez-Silva, Cristhian Neil; Ramirez, Juan Kenedy; Villarreal-La Torre, Víctor Eduardo; Arevalo, Sharon Velasquez (Ethnobotany Research and Applications, 2020)
Background: The botanical diversity of Peru has meant that the use of medicinal plants is currently being promoted in health institutions nationwide. The aim of this review is to provide scientific information to support the therapeutic properties of barberry such as Berberis vulgaris. Methods: Information was searched in scientific databases, Plantlist, Scopus, PubMed, Google Scholar and repositories of university theses on ethnobotanical and ethnopharmacological information and was compared with Berberis rigida Hieron, Berberis vulgaris, Ilex guayusa Loes, Vallesia glabra (Cav ), since all of them also have the common name of barberry. Results: Currently there are 3 families and 4 genera that present a species known as barberry, 5 Peruvian university theses stand out in the last 10 years that address the utilities of the genus Berberidaceae and its species, with the tincture being the most useful. The most scientific information, 1,363 studies between ethnobotanists and ethnopharmacologists, support the usefulness of B. vulgaris, although they come from eastern countries and only 3 are Peruvian. Conclusions: The information that supports the usefulness of B. vulgaris (barberry) comes from international publications (Iran, Pakistan), in addition there is no Peruvian ethnobotanical and ethnopharmacological scientific information, this generates a risk of species confusion, even more so if It has the same common name, and similar phytotherapeutic characteristics. These two situations would lead to the adoption of information from other countries, which in turn puts at risk of possible ineffectiveness of treatment with traditional medicine. Key words: Berberis, phytotherapeutic indication, traditional medicine, medicinal plants, barberry, secondary metabolites, berberidaceae, aquifoliaceae, apocynaceae.